KOLOREKTAL KANSERDE METASTAZIN SERUM TOTAL SİYALİK ASİT DÜZEYLERİ ÜZERİNE ETKİSİ - USLU, Ezel; BELCE, Ahmet; SEYMEN, Pınar; KÖKOĞLU, Emine (Cerrahpaşa Medical Journal, 2019)
Background and Design.- This study was designed to asses the effect of metastasis on serum total sialic acid level in patients with colorectal cancer. Results.- We measured serum total sialic acid (TSA) level by using Warren's thiobarbituric acid assay. TSA levels in healthy control, colorectal cancer without metastasis and colorectal cancer with metastasis were found as 73.2 ± 6.0 ; 73.7 ± 5.0 ; and 96.0 ± 9.0 mg NANA/dL respectively. Statistical difference between metastasis and the other two groups was significant (p < 0.001). Conclusion.- According to our results, metastasis causes the increase of serum TSA levels. We suggest that the determination of this increase may be useful for the evaluation of a possible metastatic involvement.